Unnatural narrative: a cognitive appraisal of unconventional patterns in flash fiction. - Karam, Khaled Mostafa; Shabaan, Areeg Nabil; Ebeid Khalil, Hamdy (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2025)
This study explores the innovative narrative structures employed in flash fiction through the lens of cognitive narratology. It examines how unconventional patterns – cyclical, dual, differential, and antinomic – challenge traditional narrative conventions by disrupting linear chronology and employing inventive techniques to compress meaning into sparse patterns. Drawing on insights from cognitive science, this study analyses how these unnatural narrative structures engage readers' variable cognitive capacities. Through the cognitive analysis of selected works, it highlights the intricate interplay between form and cognition, revealing how these narratives compress dense ideas into minimal spatiotemporal frames while fostering profound thematic impact. The findings position flash fiction as an innovative narrative art form uniquely suited to contemporary digital contexts, characterised by limited attention spans and the need for brevity. This research contributes to expanding cognitive narratology, offering a toolkit for understanding how unconventional narratives are constructed, interpreted, and cognitively processed.